Determination and electro-remediation of sulfamethazine using carbon nanotubes and silver nanoparticles as electrode modifiers - Barreto, Francisco Contini [UNESP]; dos Santos, Gloria Tersis Vieira [UNESP]; Leao, Alcides Lopes [UNESP]; Goonetilleke, Ashantha; Cesarino, Ivana [UNESP] (Springer Nature, 2025)
This paper discusses the development of a glassy carbon electrode (GC) for the determination and electro-remediation of sulfamethazine (SMZ) in natural waters using multi-walled carbon nanotubes (MWCNT) and silver nanoparticles (AgNPs) as electrode modifiers. The SMZ is an antibiotic found in surface and groundwater that can cause impacts for the environment and the population even at low concentrations. Therefore, it is essential to develop innovative approaches for the SMZ determination and degradation. The proposed GC electrode modifier was characterized demonstrating that the silver nanoparticles was incorporated onto the MWCNT. Voltammetric parameters of the SMZ oxidation process were optimized to improve the response in the analysis. The linearity obtained was from 0.3 to 5.0 µmol L−1, and the limit of detection and limit of quantification obtained was 0.19 µmol L−1 and 0.63 µmol L−1, respectively. This electrode was used for SMZ quantification in natural waters and interferents were used in a selectivity study. Finally, the GC/MWCNT-AgNPs was applied for the remediation of SMZ using chronoamperometry with +1.5 V for 2.5 h, decreasing 62.04% of the antibiotic. As a result, MWCNT-AgNPs were found to be an excellent option for the effective determination and remediation of the SMZ.
Keywords: Multi-walled carbon nanotubes; Natural waters; Remediation; Silver nanoparticles; Sulfamethazine